Improving Reading Literacy Rate of ALS (Alternative Learning System) Students Through Casaup-Literacy Program - Galang, Ruby T.; Arrozal, Jocelyn; Batu, Cecile B.; Cortez, Leila (Future Science / FSH-PH Publications, 2023)
ne of the imminent programs the government instituted for this concern is the Alternative Learning System (ALS) which aims at providing opportunities for students who are not succeeding in the traditional classroom setting to obtain academic credit, career exploration activities, and extended teacher/peer support in an alternative setting where the ultimate goal is that obtaining a diploma. The study aimed to determine the reading levels of the respondents before and after the administration of a reading intervention program. The Reading program was conceptualized as an extended service to enhance the reading abilities of the ALS students. It employed the descriptive type of research to gather facts and information regarding the reading performance levels of the respondents. The respondents of the study consisted of 70 students from ALS Program of the DepEd ALS Program. The researchers utilized the Functional Literacy Test (FLT) a standardized reading assessment tool which was administered before the intervention and after the reading program. T-test was used in the treatment of the data. Based on the findings; generally, the respondents’ age ranges from 15-23 with a minimal percentage of the ages 42-51. This shows that students tend to stop their education after attending basic education. The mean results of the pre-test which is 4.0294 are far behind the results of the post-test, which is 9.4411 mean, this indicates a highly significant difference is evident in the statistical treatment. A t-value of -29.583 resulted and a p-value of 0.000 was obtained from the data. This proves a high significance is displayed in the results and that the intervention program has proven its effectiveness in the reading performance of the ALS Students.